Dunes: the fight goes on - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The advance of the dunes is now a major worry for all those concerned with agriculture and the environment in Sahelian countries. The dunes pose a real threat to the infrastructure serving these countries. To combat their advance, governments and...